Overview of Nausea and Vomiting in Postoperative Patients (PONV) in the Recovery Room - Anjarwati, Nadia; Sutrisno, Resti Yulianti; Suprapti, Yuni (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2025)
Surgery requires anesthesia to reduce pain. Anesthesia can have side effects such as decreased blood pressure, pulse, nausea, and vomiting. The incidence of postoperative nausea and vomiting (PONV) is different for each person because it is influenced by several factors such as age, gender, BMI, physical status of the patient, previous history of PONV, history of motion sickness, type of action and anesthesia, and duration of surgery. The purpose of this study was to determine the factors that influence the incidence of nausea and vomiting in postoperative patients. This study used a case study research design with a cross-sectional approach. This research was conducted in the Recovery Room of the Central Surgical Installation (IBS) of Tidar Hospital, Magelang City. The population in this study was 55 respondents. The sample in this study was 48 respondents who met the inclusion and exclusion criteria. Data analysis in this study used univariate analysis with frequency and percentage and bivariate analysis with the chi-square test. The results showed that the incidence of postoperative nausea and vomiting occurred in 16.7% of respondents in the mild category and 4.2% of respondents in the moderate category. Factors that are proven to affect the incidence of nausea and vomiting in this study are the duration of surgery with a p-value of 0.001, the type of action performed with a p-value of 0.015, and a history of illness with a p-value of 0.019.